Control of ATP concentration in Escherichia coli using an ATP-sensing riboswitch for enhanced S-adenosylmethionine production. Issue 36 (24th April 2017) - Chen, Yawei; Zhou, Huiyun; Wang, Meng; Tan, Tianwei
Abstract : We proposed an ATP-sensing riboswitch-based strategy which could be applied to regulate the intracellular ATP concentration dynamically in E. coli . This strategy will be most beneficial for enhancing the production of the ATP-driven metabolites. Abstract : ATP is the limiting precursor for S-adenosylmethionine (SAM) synthesis in Escherichia coli . In contrast to traditional optimization of fermentation processes, the riboswitch-based strategy, which was developed as a novel efficient regulation approach, has been applied for the control of the intracellular ATP concentration in order to promote the production of SAM. In this work, a newly discovered ATP-sensing riboswitch yda O motif was used to balance the requirement of ATP in SAM biosynthesis. The results show that the RNA element yda O from Bacillus subtilis could play a role in regulating gene expression in E. coli . The yda O motif-based regulation strategy, which was induced by ATP, improved the ATP level as well as the titer of SAM. The intracellular SAM titer of the best-performing strain, AYV, produced the highest SAM titer (1.23 mg L −1 ) which was increased by about 55% compared with the control. Overall, the method enabled new insights into the regulation of ATP in E. coli . These results demonstrate a strategy for optimally employing an ATP-sensing riboswitch for the ATP balance of industrial ATP-driven bioprocesses.